Terrain-slope analysis in sg chuchuh using surfer software - Mohd Helrianno Bin Abdul Taufik (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Nowadays, the population growth keep increasing and a lot of demand in food production. Many land being cleared open including sloppy area for expansion of the agricultural activity to fit in this food demand. Uncontrolled cleared open of terrain-slope will lead soil erosion due to rainfall intensity of tropical rainfall region. Research facility at INSAT become more advance for better productivity and sustainability of agricultural production. If the agricultural activity continues to increase, soil erosion will happen the same as in Cameron Highland. The project study about the surveying soil topography using GPS equipment, developing contour mapping in Surfer software and effect of soil erodibility factor and length slope factor against soil erosion rate by using ULSE formula. The project implementation of collect survey data by using GPSMAP 76 CSx equipment and plotted in Surfer. The potential watershed area was determined at the contour mapping and the length-slope factor also able to determine. The organic matter of the soil sample was 5.04%. Based on the possible soil texture at INSAT, the soil erodibility was able to determine. There was significant effect of soil erodibility factor and length slope factor toward soil erosion rate by using the USLE formula. When the soil erodibility factor or length slope factor increased, the soil erosion rate will increases.